Anti-crack and anti-impact UHPC (Ultra High Performance Concrete) board based on decoration wastes and preparation method thereof
By using the micro powder and aggregate treated by decoration waste, combined with fibers and expansion agents, the cracking and impact resistance and hydration degree of UHPC plates are improved, and the impact resistance and carbon emissions of existing UHPC materials in complex environments are solved. High-quality problems have achieved efficient, environmentally friendly and economical UHPC board preparation.
Patent Information
- Application Number
- CN202411300210.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-02-07
AI Technical Summary
Existing UHPC materials lack impact resistance in complex service environments, and have high carbon emissions during production, low hydration and low impact on mechanical properties. A UHPC board that can not only improve cracking and impact resistance and hydration are needed. .
Decoration waste is used for treatment. Through the synergy between decoration waste micro powder and aggregate and fiber, the crack and impact resistance of UHPC boards is improved, and the degree of hydration and mechanical properties are improved through the use of expansion agents and water reducing agents. .
The UHPC board has achieved excellent crack and impact resistance, high strength, simple preparation process, low cost, and reduced production carbon emissions by nearly 50%, which has good environmental and economic benefits.
Smart Images

Figure BDA0005047423670000111 
Figure BDA0005047423670000121 
Figure BDA0005047423670000122
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a crack-resistant and impact-resistant UHPC board based on decoration waste and a preparation method thereof. Background Art
[0002] Ultra-high performance concrete (UHPC) is a new type of cement-based material and the most innovative cement-based engineering material in the past three decades. It has ultra-high mechanical strength and excellent weather resistance, and can be called the most durable engineering material. The mechanical properties of properly reinforced UHPC are close to those of steel structures. At the same time, UHPC has excellent wear resistance and explosion resistance. Therefore, UHPC is often used in large-span bridges, explosion-proof structures (military projects, bank vaults, etc.) and thin-walled structures, as well as in some complex and harsh service environments such as high abrasion and high corrosion environments. However, in complex service environments, UHPC concrete structures not only have to withstand static loads, but also often need to withstand non-static impact loads, such as defense projects resisting explosion loads, bridge piers bearing wave impacts, and high-rise buildings being hit by falling objects. In the above context, UHPC often has the problem of high strength but insufficient impact resistance. Therefore, it is of great value and significance to improve the crack resistance and impact resistance of UHPC.
[0003] The use of alkali-resistant fiber grid reinforced UHPC can make UHPC have the characteristics of multi-crack cracking and excellent tensile strain hardening performance, and can significantly reduce the thickness of the concrete slab. However, relevant studies have found that for thin-walled structures, excessive fiber content is not conducive to the working performance of concrete and will increase the difficulty of pouring construction. When the fiber grid reinforced concrete reaches the bearing capacity, the crack width and deflection are large, and stress concentration is prone to occur.
[0004] In addition, due to the large amount of cement used and the extremely low water-cement ratio of UHPC, its production cost and carbon dioxide emissions remain high. The hydration degree of UHPC is usually low (30-35%), and a large amount of cement clinker is not involved in hydration, which has an adverse effect on the mechanical properties and workability of UHPC, and is prone to problems such as reduced compressive strength and slowed setting speed.
[0005] The carbon emissions of the cement industry account for about 13% of the national carbon emissions, second only to the 18% of the steel industry. The high carbon emissions associated with cement production have an adverse impact on the environment. As we all know, the production of cement requires "two grindings and one burning". The carbon emissions in its production process mainly come from the high-temperature decomposition of limestone in the raw materials and the combustion of fossil fuels. The generation and discharge of construction waste in my country's cities has increased rapidly in recent years. Among them, decoration waste accounts for a considerable proportion of the mixed construction waste, including waste bricks, waste concrete, waste glass and waste wood. The long-term stacking of construction and decoration waste not only occupies land resources, but also easily causes environmental problems such as groundwater pollution. Therefore, a resource-based treatment method for decoration waste is urgently needed.
[0006] Chinese patent CN117550835A "A UHPC explosion-proof panel and its preparation method" discloses a UHPC explosion-proof panel including a flexible buffer energy absorption layer and a rigid protective layer glued on both sides of the flexible buffer energy absorption layer, which improves the impact resistance of UHPC through a multi-layer design. However, its impact resistance still needs to be further improved, and the influence of the hydration degree of UHPC on the working performance of concrete has not been studied.
[0007] Therefore, in order to realize the concept of green and sustainable development of my country's construction industry, it is of great significance to provide a UHPC board and its preparation method which have excellent crack resistance and impact resistance, improve the hydration degree of UHPC, and improve the crack resistance and impact resistance of various components of decoration waste. Summary of the invention
[0008] In view of the fact that the impact resistance of existing UHPC materials still needs to be further improved, and the influence of the hydration degree of UHPC on the working performance of concrete has not been studied, and at the same time, a resource-based treatment method for decoration waste is urgently needed, the present invention provides a crack-resistant and impact-resistant UHPC board based on decoration waste and a preparation method thereof, which processes the decoration waste, and high-values the components of the decoration waste and utilizes them on a large scale, which can effectively alleviate the problem of high carbon emissions in the construction industry. The expansion agent, decoration waste aggregate and fiber work synergistically to improve the crack resistance and impact resistance of the UHPC board. The crack-resistant and impact-resistant UHPC board based on decoration waste has the advantages of excellent crack resistance and impact resistance, high strength, simple preparation process, low cost, etc., and the preparation process does not require calcination or steaming, and is low-carbon and environmentally friendly.
[0009] To achieve the above object, the technical solution adopted by the present invention is:
[0010] A crack-resistant and impact-resistant UHPC board based on decoration waste comprises the following components by weight: 120-200 parts of ordinary Portland cement, 60-80 parts of slag, 60-90 parts of decoration waste powder, 200-300 parts of decoration waste aggregate, 20-40 parts of steel fiber, 4-8 parts of waste fiber, 8-15 parts of expansion agent, 3-6 parts of water reducer and 50-60 parts of water.
[0011] Furthermore, the decoration waste powder is prepared by the following method:
[0012] The waste concrete, waste bricks and waste mortar are mixed, crushed, added with a composite modifier, and ground for 30-60 minutes to obtain the decoration waste fine powder.
[0013] Furthermore, the composite modifier is at least two of sodium hydroxide, sodium carbonate and sodium bicarbonate; the ratio of the composite modifier to the total weight of waste concrete, waste bricks and waste mortar is 1:(30-50).
[0014] Furthermore, the specific surface area of the decoration waste powder is greater than 450m 2 / kg.
[0015] Furthermore, the fineness of the crack-resistant and impact-resistant UHPC board based on renovation waste is 20-30%.
[0016] Furthermore, the decoration waste aggregate is a mixture of waste glass aggregate and waste concrete aggregate; the particle size of the decoration waste aggregate is 0.3-4.75 mm.
[0017] Furthermore, the waste fibers are made from waste wood and waste fabrics; and the length of the waste fibers is 6-10 mm.
[0018] Furthermore, the expansion agent is one or more of calcium oxide, magnesium oxide, and calcium sulfoaluminate.
[0019] Furthermore, the water reducer is a polycarboxylic acid-based water reducer; and the water reduction rate of the water reducer is ≥35%.
[0020] Furthermore, the thickness of the crack-resistant and impact-resistant UHPC board based on decoration waste is 10-20 mm.
[0021] Another object of the present invention is to provide a method for preparing a crack-resistant and impact-resistant UHPC board based on decoration waste.
[0022] A method for preparing a crack-resistant and impact-resistant UHPC board based on decoration waste according to any of the above items comprises the following steps:
[0023] S1. Weigh ordinary Portland cement, slag, decoration waste powder, decoration waste aggregate, and expansion agent according to the required ratio, mix, and stir slowly for 60-80s to obtain a mixed dry material;
[0024] S2. Weigh water and water reducing agent, pour into the mixed dry material obtained in S1, stir for 6-8 minutes, add steel fiber and waste fiber, mix well, pour the slurry into the mold and vibrate;
[0025] S3. After curing in a standard curing room for 1 day, the mold is removed and the plate is placed in a standard curing room for sealed curing to obtain the crack-resistant and impact-resistant UHPC plate based on decoration waste.
[0026] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0027] The crack-resistant and impact-resistant UHPC board based on decoration waste provided by the present invention uses decoration waste powder prepared by composite modification of a mixture of waste concrete, waste bricks and waste mortar as a cementitious material, and fully stimulates the volcanic ash activity of the mixture through a composite modifier, so that the decoration waste powder can release active calcium ions, active silicon ions and active aluminum ions, which is beneficial to the formation of hydration products, thereby improving the mechanical properties of the UHPC board. At the same time, the decoration waste powder can have a bridging effect and penetrate into large and small cracks inside the concrete, which helps to prevent the expansion and connection of the cracks, thereby improving the shrinkage of the UHPC board and effectively filling The micro-voids in the concrete can be filled to limit the migration and evaporation of water, and the mechanical properties can be further improved. The decoration waste aggregate made from a mixture of waste glass aggregate and waste concrete aggregate can be used as aggregate. Through the reaction of the aggregate with the alkaline ions in the slurry, it has a certain expansion effect, which can improve the early shrinkage of the concrete and the shrinkage resistance of the UHPC board, thereby improving its crack resistance. At the same time, the silicate component in the decoration waste aggregate will react with the calcium hydroxide produced by the hydration of cement to generate hydrated calcium silicate, which improves the bonding between the aggregate and the surrounding area. The synergistic effect of the two can improve the hydration degree of the UHPC board and improve its mechanical properties and shrinkage resistance.
[0028] The present invention improves the crack resistance and impact resistance of the UHPC board by adding an expansion agent, decoration waste aggregate and mixed fiber. The steel fiber can significantly improve the tensile strength and toughness of the UHPC board. The waste fiber has a low elastic modulus and is evenly distributed in the concrete to form a three-dimensional support network, which can effectively resist the generation and development of cracks in the UHPC board, improve the crack resistance of the concrete board and improve the microstructure of the UHPC board. The waste fiber has good water absorption and water retention. The moisture is gradually released in the later stage, which helps to maintain the humidity inside the concrete stable and can serve as an internal curing material, thereby avoiding shrinkage caused by excessive water loss in the concrete. The decoration waste aggregate has a certain expansion effect, and synergistically acts with the steel fiber, the waste fiber and the expansion agent to inhibit the expansion of microcracks before the matrix cracks, significantly improve the initial crack strength of the UHPC board, effectively transfer loads at multiple cracks, disperse the stress concentration effect on the main crack, and generate more dense cracks through local force transmission efficiency, which can effectively increase the plastic deformation of the UHPC board and improve the toughness and crack resistance and impact resistance of the UHPC board.
[0029] The present invention provides a crack-resistant and impact-resistant UHPC board based on decoration waste, which has the characteristics of high strength, fast early strength development rate, good crack resistance and impact resistance, etc., fully utilizes various components in the decoration waste, greatly reduces the amount of cement, and its production carbon emission is reduced by nearly 50% compared with traditional UHPC boards. It has low cost, wide sources, and good environmental and economic benefits. DETAILED DESCRIPTION
[0030] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention is further described by the following examples. Obviously, the following examples are only part of the embodiments of the present invention, rather than all the embodiments; it should be understood that the embodiments of the present invention are only used to illustrate the technical effects of the present invention, rather than to limit the scope of protection of the present invention.
[0031] The raw materials in the examples can all be obtained commercially; unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0032] The decoration waste powders described in the following examples are all prepared by the following preparation method, which comprises the following steps:
[0033] 40 parts of waste concrete, waste bricks and waste mortar are mixed and crushed, and 1 part of sodium hydroxide, sodium carbonate and sodium bicarbonate are added, and ground for 45 minutes to obtain the decoration waste powder, whose specific surface area is greater than 450m 2 / kg.
[0034] Example 1
[0035] A method for preparing a crack-resistant and impact-resistant UHPC board based on decoration waste comprises the following steps:
[0036] The crack-resistant and impact-resistant UHPC board based on decoration waste includes 200 parts of ordinary Portland cement, 60 parts of slag, 60 parts of decoration waste powder, 300 parts of decoration waste aggregate (particle size is 0.3-4.75 mm), 40 parts of steel fiber, 4 parts of waste fiber (length is 6-10 mm), 15 parts of magnesium oxide expansion agent, 3 parts of polycarboxylic acid water reducer, and 60 parts of water.
[0037] S1. Weigh ordinary Portland cement, slag, decoration waste powder, decoration waste aggregate, and expansion agent according to the required ratio, mix, and stir slowly for 70s to obtain a mixed dry material;
[0038] S2. Weigh water and water reducing agent, pour into the mixed dry material obtained in S1, stir for 6 minutes, add steel fiber and waste fiber, mix thoroughly, pour the slurry to fill the mold and vibrate, the thickness is 10mm;
[0039] S3. After curing in a standard curing room for 1 day, the mold is removed and the plate is placed in a standard curing room for sealed curing to obtain the crack-resistant and impact-resistant UHPC plate based on decoration waste.
[0040] Example 2
[0041] A method for preparing a crack-resistant and impact-resistant UHPC board based on decoration waste comprises the following steps:
[0042] The crack-resistant and impact-resistant UHPC board based on decoration waste includes 120 parts of ordinary Portland cement, 80 parts of slag, 90 parts of decoration waste powder, 200 parts of decoration waste aggregate (particle size is 0.3-4.75 mm), 25 parts of steel fiber, 8 parts of waste fiber (length is 6-10 mm), 18 parts of calcium oxide expansion agent, 6 parts of polycarboxylic acid water reducer, and 50 parts of water.
[0043] S1. Weigh ordinary Portland cement, slag, decoration waste powder, decoration waste aggregate, and expansion agent according to the required ratio, mix, and stir slowly for 70s to obtain a mixed dry material;
[0044] S2. Weigh water and water reducing agent, pour into the mixed dry material obtained in S1, stir for 8 minutes, add steel fiber and waste fiber, mix thoroughly, pour the slurry to fill the mold and vibrate, the thickness is 20mm;
[0045] S3. After curing in a standard curing room for 1 day, the mold is removed and the plate is placed in a standard curing room for sealed curing to obtain the crack-resistant and impact-resistant UHPC plate based on decoration waste.
[0046] Comparative Example 1
[0047] A method for preparing a UHPC board comprises the following steps:
[0048] The UHPC board includes 200 parts of ordinary Portland cement, 60 parts of slag, 60 parts of decoration waste powder, 300 parts of decoration waste aggregate (particle size is 0.3-4.75mm), 40 parts of steel fiber, 4 parts of waste fiber (length is 6-10mm), 3 parts of polycarboxylic acid water reducer, and 60 parts of water.
[0049] S1. Weigh ordinary Portland cement, slag, decoration waste powder, and decoration waste aggregate according to the required ratio, mix, and stir slowly for 70s to obtain a mixed dry material;
[0050] S2. Weigh water and water reducing agent, pour into the mixed dry material obtained in S1, stir for 6 minutes, add steel fiber and waste fiber, mix thoroughly, pour the slurry to fill the mold and vibrate, the thickness is 10mm;
[0051] S3. After curing in a standard curing room for 1 day, the mold is removed and the panel is placed in a standard curing room for sealed curing to obtain the UHPC panel.
[0052] Compared with Example 1, the main difference of this comparative example is that no swelling agent is added.
[0053] Comparative Example 2
[0054] A method for preparing a UHPC board comprises the following steps:
[0055] The UHPC board comprises 200 parts of ordinary Portland cement, 60 parts of slag, 60 parts of decoration waste powder, 300 parts of decoration waste aggregate (particle size is 0.3-4.75 mm), 15 parts of magnesium oxide expansion agent, 3 parts of polycarboxylic acid water reducing agent, and 60 parts of water.
[0056] S1. Weigh ordinary Portland cement, slag, decoration waste powder, decoration waste aggregate, and expansion agent according to the required ratio, mix, and stir slowly for 70s to obtain a mixed dry material;
[0057] S2. Weigh water and water reducing agent, pour into the mixed dry material obtained in S1, stir for 6 minutes, mix thoroughly, pour the slurry into the mold and vibrate it, the thickness is 10mm;
[0058] S3. After curing in a standard curing room for 1 day, the mold is removed and the panel is placed in a standard curing room for sealed curing to obtain the UHPC panel.
[0059] Compared with Example 1, the main difference of this comparative example is that no fiber is added.
[0060] Comparative Example 3
[0061] A method for preparing a UHPC board comprises the following steps:
[0062] The UHPC board includes 200 parts of ordinary Portland cement, 60 parts of slag, 300 parts of decoration waste aggregate (particle size is 0.3-4.75 mm), 40 parts of steel fiber, 4 parts of waste fiber (length is 6-10 mm), 15 parts of magnesium oxide expansion agent, 3 parts of polycarboxylic acid water reducer, and 60 parts of water.
[0063] S1. Weigh ordinary Portland cement, slag, decoration waste aggregate, and expansion agent according to the required ratio, mix, and stir slowly for 70s to obtain a mixed dry material;
[0064] S2. Weigh water and water reducing agent, pour into the mixed dry material obtained in S1, stir for 6 minutes, add steel fiber and waste fiber, mix thoroughly, pour the slurry to fill the mold and vibrate, the thickness is 10mm;
[0065] S3. After curing in a standard curing room for 1 day, the mold is removed and the panel is placed in a standard curing room for sealed curing to obtain the UHPC panel.
[0066] Compared with Example 1, the main difference of this comparative example is that no decoration waste powder is added.
[0067] Comparative Example 4
[0068] A method for preparing a UHPC board comprises the following steps:
[0069] The UHPC board includes 200 parts of ordinary Portland cement, 60 parts of slag, 60 parts of decoration waste powder, 40 parts of steel fiber, 4 parts of waste fiber (length is 6-10mm), 15 parts of magnesium oxide expansion agent, 3 parts of polycarboxylic acid water reducer, and 60 parts of water.
[0070] S1. Weigh ordinary Portland cement, slag, decoration waste powder, and expansion agent according to the required ratio, mix, and stir slowly for 70s to obtain a mixed dry material;
[0071] S2. Weigh water and water reducing agent, pour into the mixed dry material obtained in S1, stir for 6 minutes, add steel fiber and waste fiber, mix thoroughly, pour the slurry into the mold and vibrate it, the thickness is 10mm;
[0072] S3. After curing in a standard curing room for 1 day, the mold is removed and the panel is placed in a standard curing room for sealed curing to obtain the UHPC panel.
[0073] Compared with Example 1, the main difference of this comparative example is that no decoration waste aggregate is added.
[0074] The above embodiment and comparative example (plate thickness = 12 mm) were subjected to performance tests, and the experimental test method was as follows:
[0075] Working performance: Tested according to JGJ / T 70-2009 "Test Methods for Basic Performance of Building Mortar". Flow diameter is an important indicator for evaluating the working performance of concrete. The larger the flow diameter, the worse the working performance.
[0076] Mechanical properties: The compressive strength is based on GB / T 50081-2019 "Test methods and standards for physical and mechanical properties of concrete", and a 100mm×100mm×100mm cubic test block is prepared for each group; the flexural strength is tested according to GB / T 17671-2021 "Cement mortar strength test method", and the specimen size is 40mm×40mm×160mm.
[0077] Drying shrinkage: The test is carried out according to the contact method specified in GB / T 50082-2009 "Standard for Test Methods of Long-term Properties and Durability of Ordinary Concrete", and the specimen size is 100mm×100mm×515mm.
[0078] Impact resistance test: The specimen size is 300mm×300mm×12mm. The impact resistance of different groups of concrete specimens was evaluated. A 3m long plastic pipe was used as the path of the steel ball. A 1.1kg iron ball was dropped vertically. After 100 cycles, the changes in the concrete slab were observed. The energy conversion of the steel ball was calculated using the energy formula.
[0079] E=0.5×m×v2
[0080] E-Impact Energy
[0081] m- ball mass
[0082] v-ball speed
[0083] The result is as follows:
[0084] ①Working performance
[0085] Table 1 Flow diameters of Examples 1-2 and Comparative Examples 1-4 of the present invention
[0086] serial number Flow diameter(mm) Example 1 288 Example 2 283 Comparative Example 1 292 Comparative Example 2 325 Comparative Example 3 312 Comparative Example 4 316
[0087] As can be seen from Table 1, the crack-resistant and impact-resistant UHPC board based on decoration waste prepared by the technical solution of the present invention has a flow diameter of up to 283mm and good working performance. Comparative Example 1 does not add expansion agent, and the flow diameter is somewhat different from that of each embodiment; Comparative Example 2 does not add steel fiber and waste fiber, and the flow diameter is 325mm, which is 12.8% higher than that of Example 1; while Comparative Example 3 does not add decoration waste powder, the flow diameter is 312mm, and the working performance is poor; Comparative Example 4 does not add decoration waste aggregate, the flow diameter is 316mm, and the working performance is poor.
[0088] ② Mechanical properties
[0089] Table 2 Mechanical properties of Examples 1-2 and Comparative Examples 1-4 of the present invention
[0090] serial number 28-day compressive strength (MPa) 28-day flexural strength (MPa) Example 1 136.8 26.8 Example 2 137.6 27.1 Comparative Example 1 131.2 23.4 Comparative Example 2 121.2 17.2 Comparative Example 3 124.5 24.5 Comparative Example 4 129.5 23.2
[0091] As can be seen from Table 2, the crack-resistant and impact-resistant UHPC board based on decoration waste prepared by the technical solution of the present invention has a 28-day compressive strength of up to 137.6 MPa and a 28-day flexural strength of more than 25 MPa, and has excellent mechanical properties.
[0092] Comparative Example 1 did not add an expansion agent, and its 28-day compressive strength decreased by 4.4% to 131.2 MPa, and its 28-day flexural strength decreased by 12.7% to 23.4 MPa compared with Example 1; Comparative Example 2 did not add fiber, and its compressive strength and flexural strength decreased by 11.4% and 35.8% respectively compared with Example 1, and the 28-day flexural strength was less than 20 MPa, indicating that the fiber can effectively hinder the expansion of microcracks inside the concrete; Comparative Example 3 did not add decoration waste powder, and the compressive strength was 124.5 MPa, and the mechanical properties were poor; Comparative Example 4 did not add decoration waste aggregate, and the compressive strength and flexural strength were poor compared with the embodiments, and the mechanical properties were poor.
[0093] ③ Anti-shrinkage performance
[0094] Table 3 Drying shrinkage values of Examples 1-2 and Comparative Examples 1-4 of the present invention
[0095]
[0096]
[0097] It can be seen from Table 3 that the drying shrinkage value of each group of samples gradually increases with the increase of age. The crack-resistant and impact-resistant UHPC panels based on decoration waste prepared by the technical solution of the present invention have a 56-day drying shrinkage value of 278-290 μm / m in each embodiment, which has excellent anti-shrinkage performance.
[0098] Under the same conditions, the 56-day drying shrinkage value of Comparative Example 1 without adding an expansion agent is 382 μm / m, which is 137.4% of the 56-day drying shrinkage value of Example 1, showing poor anti-shrinkage performance; while Comparative Example 2 without adding fiber has a 56-day drying shrinkage value of 492 μm / m, which is 77.0% higher than that of Example 1, far inferior to the performance of each embodiment; Comparative Example 3 without adding decoration waste powder has a lower early drying shrinkage value among all the comparative examples, but there is a certain gap with the embodiments in the later period, and the anti-shrinkage performance is general; Comparative Example 4 without adding decoration waste aggregate has a 56-day drying shrinkage value of 356 μm / m, and the anti-shrinkage performance is poor.
[0099] ④Impact resistance
[0100] Table 4 Impact failure state of Examples 1-2 and Comparative Examples 1-4 of the present invention
[0101]
[0102] It can be seen from Table 4 that the crack-resistant and impact-resistant UHPC plates based on decoration waste prepared by the technical solution of the present invention have 37 impact times required to produce the first crack in Example 1 and 39 impact times required to produce the first crack in Example 2, showing excellent crack resistance and impact resistance.
[0103] Under the same conditions, in Comparative Example 1, no expansion agent was added, and the number of impacts required to produce the first crack was 29 times, which was poorer than that in Example 1; while in Comparative Example 2, no fiber was added, and the number of impacts required to produce the first crack was the lowest, which was 18 times, indicating that the addition of fiber and expansion agent can significantly improve the impact resistance of concrete slabs; in Comparative Example 3, no decoration waste powder was added, and in Comparative Example 4, no decoration waste aggregate was added, and the number of impacts required to produce the first crack were 35 times and 33 times respectively, and the crack resistance and impact resistance were better in the comparative examples, but still could not be compared with the embodiments.
[0104] In summary, the present invention selects ordinary silicate cement, slag, decoration waste powder, decoration waste aggregate, steel fiber, waste fiber, expansion agent, and water reducer to prepare the crack-resistant and impact-resistant UHPC board based on decoration waste. By using decoration waste powder as a cementitious material and decoration waste aggregate as an aggregate, it is beneficial to the generation of hydration products and has a certain expansion effect, which can improve the hydration degree of the UHPC board and improve its mechanical properties and shrinkage resistance. By adding expansion agent, decoration waste aggregate and mixed fiber to jointly improve the UHPC The crack resistance and impact resistance of the board, the fibers are evenly distributed in the concrete to form a three-dimensional support network, which can effectively resist the generation and development of cracks in the UHPC board, improve the crack resistance of the concrete board and improve the microstructure of the UHPC board, significantly improve the tensile strength and toughness of the UHPC board, and the decoration waste aggregates synergize with the steel fibers, waste fibers, and expansion agents to inhibit the expansion of microcracks before the matrix cracks, significantly improve the initial crack strength of the UHPC board, and effectively increase the plastic deformation of the UHPC board, and improve the toughness and crack resistance and impact resistance of the UHPC board. The crack-resistant and impact-resistant UHPC board based on decoration waste of the present invention has the characteristics of high strength, fast early strength development rate, good crack resistance and impact resistance, etc., makes full use of various components in decoration waste, greatly reduces the amount of cement, and its production carbon emissions are reduced by nearly 50% compared with traditional UHPC boards, with low cost, wide sources, good environmental and economic benefits, suitable for large-scale promotion and industrialized production, and has positive significance for promoting the sustainable development of the construction industry.
[0105] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A crack-resistant and impact-resistant UHPC board based on decoration waste, characterized in that: Calculated by weight, the composition includes: 120-200 parts of ordinary Portland cement, 60-80 parts of slag, 60-90 parts of decoration waste powder, 200-300 parts of decoration waste aggregate, 20-40 parts of steel fiber, 4-8 parts of waste fiber, 8-15 parts of expansion agent, 3-6 parts of water reducer and 50-60 parts of water.
2. A crack-resistant and impact-resistant UHPC board based on renovation waste according to claim 1, characterized in that: The decoration waste powder is prepared by the following method: The waste concrete, waste bricks and waste mortar are mixed, crushed, added with a composite modifier, and ground for 30-60 minutes to obtain the decoration waste fine powder.
3. A crack-resistant and impact-resistant UHPC board based on renovation waste according to claim 2, characterized in that: The composite modifier is at least two of sodium hydroxide, sodium carbonate and sodium bicarbonate; the ratio of the composite modifier to the total weight of waste concrete, waste bricks and waste mortar is 1:(30-50).
4. A crack-resistant and impact-resistant UHPC board based on renovation waste according to claim 1, characterized in that: The specific surface area of the decoration waste powder is greater than 450m 2 / kg.
5. A crack-resistant and impact-resistant UHPC board based on renovation waste according to claim 1, characterized in that: The decoration waste aggregate is a mixture of waste glass aggregate and waste concrete aggregate; the particle size of the decoration waste aggregate is 0.3-4.75 mm.
6. A crack-resistant and impact-resistant UHPC board based on renovation waste according to claim 1, characterized in that: The waste fibers are made from waste wood and waste fabrics; and the length of the waste fibers is 6-10 mm.
7. A crack-resistant and impact-resistant UHPC board based on renovation waste according to claim 1, characterized in that: The expansion agent is one or more of calcium oxide, magnesium oxide, and calcium sulfoaluminate.
8. A crack-resistant and impact-resistant UHPC board based on renovation waste according to claim 1, characterized in that: The water reducing agent is a polycarboxylic acid-based water reducing agent; the water reducing rate of the water reducing agent is ≥35%.
9. A crack-resistant and impact-resistant UHPC board based on renovation waste according to claim 1, characterized in that: The thickness of the crack-resistant and impact-resistant UHPC board based on renovation waste is 10-20 mm.
10. A method for preparing a crack-resistant and impact-resistant UHPC board based on decoration waste according to any one of the preceding claims, characterized in that: The following steps are involved: S1. Weigh ordinary Portland cement, slag, decoration waste powder, decoration waste aggregate, and expansion agent according to the required ratio, mix, and stir slowly for 60-80s to obtain a mixed dry material; S2. Weigh water and water reducing agent, pour into the mixed dry material obtained in S1, stir for 6-8 minutes, add steel fiber and waste fiber, mix well, pour the slurry into the mold and vibrate; S3. After curing in a standard curing room for 1 day, the mold is removed and the plate is placed in a standard curing room for sealed curing to obtain the crack-resistant and impact-resistant UHPC plate based on decoration waste.
Citation Information
Patent Citations
UHPC explosion-proof plate and preparation method thereof
CN117550835A